2003
DOI: 10.2139/ssrn.444141
|View full text |Cite
|
Sign up to set email alerts
|

Voter Preferences and State Regulation of Smoking

Abstract: Voters' preferences for smoking restrictions in restaurants, bars, malls, indoor sporting events, and hospitals are consistent with state-level restrictions on smoking in each of these public areas. This analysis is based on constructed measures of political pressure that take into account both individual preferences and voting behavior. Although smokers are less likely to vote than nonsmokers, their lower voting rate does not substantially influence the probability that a state has a restriction. Other factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Hence, if a state adopts any degree of restriction (i.e., 1 through 5 in Alciati et al, 1998), then the corresponding measure in our model is assigned a value of 1. Other studies (i.e., Boyes and Marlow, 1996;Chaloupka and Saffer, 1992;Gallet, Hoover, and Lee, 2006;Hersch, Del Rossi, and Viscusi, 2004) also use dichotomous variables to account for anti-smoking laws, and so our model and estimation results are most comparable to the literature. 4.…”
Section: Determinants Of Youth Access Restrictionsmentioning
confidence: 59%
See 2 more Smart Citations
“…Hence, if a state adopts any degree of restriction (i.e., 1 through 5 in Alciati et al, 1998), then the corresponding measure in our model is assigned a value of 1. Other studies (i.e., Boyes and Marlow, 1996;Chaloupka and Saffer, 1992;Gallet, Hoover, and Lee, 2006;Hersch, Del Rossi, and Viscusi, 2004) also use dichotomous variables to account for anti-smoking laws, and so our model and estimation results are most comparable to the literature. 4.…”
Section: Determinants Of Youth Access Restrictionsmentioning
confidence: 59%
“…Different stories can be told for this variable affecting the likelihood of states adopting youth access restrictions. For instance, since Hersch, Del Rossi, and Viscusi (2004) and Gallet, Hoover, and Lee (2006) find more conservative states are less likely to adopt smoking bans, which may be due to them favoring less government involvement in markets, it may be that more conservative states are less likely to adopt youth access restrictions. Alternatively, it may be that more conservative states promote parental control, making it more likely to restrict youth access to tobacco.…”
Section: Determinants Of Youth Access Restrictionsmentioning
confidence: 99%
See 1 more Smart Citation
“…61 The notable exceptions are Bartholomew and Abouk (2016) and Bharadwaj, Johnsen, and Løken (2014), which separately estimate the effect bans on smoking and nonsmoking mothers. 62 Previous work has shown anti-smoking legislation (and the timing of adoption) depends on a number of factors that relate directly to maternal smoking and child health (Chaloupka and Saffer 1992;Boyes and Marlow 1996;Ohsfeldt and Boyle 1999;Dunham and Marlow 2000;Hersch, Del Rossi, and Kip Viscusi 2004;Gallet, Hoover, and Lee 2006;Pakko 2006;Fleck and Hanssen 2008;Smith et al 2008;Golden, Ribisl, and Perreira 2014;Nikaj, Miller and Taurus 2016). 63 While at the national level the prevalence of smoking bans is positively correlated with cigarette taxes (see Figure 2) at the sub-national level bans, taxes, and other instruments may act as substitutes or complements; previous studies have found evidence consistent with both substitution and complementarity (Gallet, Hoover, and Lee 2006;Golden, Ribisl, and Perreira 2014).…”
Section: Endogeneity Of Policiesmentioning
confidence: 99%
“…This is a general finding in the literature. Hersch et al (2004), for instance, demonstrate that smoking regulation is the outcome of a complex interaction between economic arguments, interest group behavior and social preferences. Burda and Weil (2001) show that restrictions on Sunday trading are important 2 if external effects of ruinous competition exist.…”
mentioning
confidence: 99%